Social determinants of health and lung cancer surgery: a qualitative study - Teteh, Dede K.; Ferrell, Betty; Okunowo, Oluwatimilehin; Downie, Aidea; Erhunmwunsee, Loretta; Montgomery, Susanne B.; Raz, Dan; Kittles, Rick; Kim, Jae Y.; Sun, Virginia (Frontiers in Public Health, 2023)
Introduction Social determinants of health (SDOH) are non-clinical factors that may affect the outcomes of cancer patients. The purpose of this study was to describe the influence of SDOH factors on quality of life (QOL)-related outcomes for lung cancer surgery patients. Methods Thirteen patients enrolled in a randomized trial of a dyadic self-management intervention were invited and agreed to participate in semi-structured key informant interviews at study completion (3 months post-discharge). A conventional content analysis approach was used to identify codes and themes that were derived from the interviews. Independent investigators coded the qualitative data, which were subsequently confirmed by a second group of independent investigators. Themes were finalized, and discrepancies were reviewed and resolved. Results Six themes, each with several subthemes, emerged. Overall, most participants were knowledgeable about the concept of SDOH and perceived that provider awareness of SDOH information was important for the delivery of comprehensive care in surgery. Some participants described financial challenges during treatment that were exacerbated by their cancer diagnosis and resulted in stress and poor QOL. The perceived impact of education varied and included its importance in navigating the healthcare system, decision-making on health behaviors, and more economic mobility opportunities. Some participants experienced barriers to accessing healthcare due to insurance coverage, travel burden, and the fear of losing quality insurance coverage due to retirement. Neighborhood and built environment factors such as safety, air quality, access to green space, and other environmental factors were perceived as important to QOL. Social support through families/friends and spiritual/religious communities was perceived as important to postoperative recovery. Discussion Among lung cancer surgery patients, SDOH factors can impact QOL and the patient’s survivorship journey. Importantly, SDOH should be assessed routinely to identify patients with unmet needs across the five domains. SDOH-driven interventions are needed to address these unmet needs and to improve the QOL and quality of care for lung cancer surgery patients.